2017
DOI: 10.1002/2017gl073159
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of ammonia on Jupiter from a preliminary inversion of Juno microwave radiometer data

Abstract: The Juno microwave radiometer measured the thermal emission from Jupiter's atmosphere from the cloud tops at about 1 bar to as deep as a hundred bars of pressure during its first flyby over Jupiter (PJ1). The nadir brightness temperatures show that the Equatorial Zone is likely to be an ideal adiabat, which allows a determination of the deep ammonia abundance in the range 362−33+33 ppm. The combination of Markov chain Monte Carlo method and Tikhonov regularization is studied to invert Jupiter's global ammonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
233
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 132 publications
(272 citation statements)
references
References 28 publications
35
233
4
Order By: Relevance
“…The ammonia abundance appears to be largely correlated with latitude rather than with absolute radiance and increases steadily toward the equator. Notably, the Juno Microwave Radiometer (MWR) also observed a sharp increase of ammonia moving southward from typical hot spot latitudes [Li et al, 2017], though the track of MWR did not overpass any of our observed features during the PJ1 passage. A comparison against the in situ measurements by the Galileo Probe mass spectrometer (GPMS [Atreya et al, 1999;Wong et al, 2004]) or the values derived from probe's radio attenuation data (RA) [Folkner et al, 1998] can be properly performed only taking into account the actual pressure range probed by the JIRAM data.…”
Section: Hot Spot #1mentioning
confidence: 57%
“…The ammonia abundance appears to be largely correlated with latitude rather than with absolute radiance and increases steadily toward the equator. Notably, the Juno Microwave Radiometer (MWR) also observed a sharp increase of ammonia moving southward from typical hot spot latitudes [Li et al, 2017], though the track of MWR did not overpass any of our observed features during the PJ1 passage. A comparison against the in situ measurements by the Galileo Probe mass spectrometer (GPMS [Atreya et al, 1999;Wong et al, 2004]) or the values derived from probe's radio attenuation data (RA) [Folkner et al, 1998] can be properly performed only taking into account the actual pressure range probed by the JIRAM data.…”
Section: Hot Spot #1mentioning
confidence: 57%
“…Because the meridional variation of brightness temperature (~30 K) is much larger than possible temperature variations, a meridionally uniform temperature profile was assumed. The retrievals follow the hybrid approach given by Li et al [2017]. First, the deep ammonia abundance is derived by using the nadir brightness temperatures of the six channels near the equator, assuming that the atmosphere is an ideal moist adiabat, because it is where the brightness temperatures are lowest.…”
Section: Resultsmentioning
confidence: 99%
“…A 3‐D turbulent signature would suggest that the winds at the cloud layer are connected to the winds deeper down (Busse, ), but a 2‐D signature might suggest the opposite, that the winds at the cloud layer are shallow and not strongly coupled to the dynamics of the deeper planet (Ingersoll & Cuzzi, ). As new data are being acquired from the Juno mission, these theories may need to be (Bolton et al, ; Kaspi et al, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%